2012
DOI: 10.1016/j.ijengsci.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

A diffusion and curvature dependent surface elastic model with application to stress analysis of anode in lithium ion battery

Abstract: a b s t r a c tThe present paper investigates the influences of surface tension and the stress distribution in the bulk induced by the surface tension, surface curvature and ions' diffusion on the elastic properties of nanostructures. In the electro-chemical diffusion process, the surface tension, ions diffusion and stress distribution will strongly dependent with each other. Here, considering the curvature effect, a surface elastic model coupled with the ions diffusion is proposed. In the model, the coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…It is well-known that materials degradation is directly correlated to the change in their geometric characteristics during electrochemical cycling 30 31 . The distributions of the two representative principal curvatures, which can be used to identify convex and concave surface, are evaluated on a statistical analysis of all particles ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that materials degradation is directly correlated to the change in their geometric characteristics during electrochemical cycling 30 31 . The distributions of the two representative principal curvatures, which can be used to identify convex and concave surface, are evaluated on a statistical analysis of all particles ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the past several years, many previous works [14,[17][18][19][20][21] studied the influence of surface stresses in modelling the stress distribution in LIBs when the size of the electrodes is in the nanometre range and found that nano-electrodes with suitable structure and size could be strengthened by surface stresses which can effectively inhibit crack formation. This conclusion is also valid for our study.…”
Section: (B) Effects Of Surface Stress and Solute Concentration On Stress Concentrationmentioning
confidence: 99%
“…In the stress analysis of electrodes in LIBs, Cheng's group first studied the surface effect on the diffusion-induced stresses in spherical particle electrodes [17] and nanowire electrodes [18]. Zang & Zhao [19] introduced the effects of diffusion together with the Tolman length into the conventional theory of surface elasticity and applied it to study the diffusion-stress coupling problems in nano-structured silicon electrodes. Hao et al [20] studied the effect of surface stress on the diffusion-induced stresses of electrode nanomaterials in LIBs with different boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Cheng studied the influence of surface mechanics on DIS within spherical nanoparticles [12]. Many experiments and theories indicated that the morphology of the electrode can affect the DIS because of the diffusion of lithium-ion [14][15][16]. DeLuca et al [17] developed a fully coupled diffusion-elasticity model to study the effects of particle morphology and size on stress generation during lithiumion insertion into Si particles.…”
Section: Introductionmentioning
confidence: 99%